Digital social work tools for practice with individuals, organizations, and communities - Freddolino, Paul P.; Goldkind, Lauri 1969-; Wolf, Lea 1970- (Oxford University Press, 2019)
" In a rapidly advancing technological culture, social work practitioners are frequently challenged to invent new strategies to meet client needs and foster social change. Despite the Council on Social Work Education's new standards for technology in social work practice, few schools of social work teach the use of technology for practice, and many instructors struggle with the integration this increasingly necessary dimension into education. Digital Social Work is designed to offer engaging, meaningful, and easy-to-use technology content that can be incorporated into generalist and advanced social work practice courses. The chapters in this volume offer instructors and students insight into the knowledge, skills, and values required of those who practice social work 2.0; by providing concrete examples of technology tools, they complement traditional social work curricula dealing with micro, mezzo, and macro systems. Chapters can be used singly--to augment Practice, Research, or Policy courses--or can provide a format to discuss technology in courses addressing practice with individuals, youth, and families. Virtual worlds, social media, GIS, blogs, and many other technology tools are represented in this collection. "--